Sosialiasi Dampak Penggunaan Gadget Terhadap Perilaku Sosial Ekonomi Anak Usia Sekolah Dasar - Hendri Dony Hahury; Nasya Nasyila Sugiarto; Hermi Oppier; Lestari Dewi Anakoda; Jeanee Belthia Nikijuluw (I-Com: Indonesian Community Journal, 2025)
The impact of gadget use on the social and economic behavior of school-age children is very complex and requires serious attention from various groups, especially parents, educators and the community. It is acknowledged that gadgets can provide benefits in terms of access to information and education, but uncontrolled use can cause various social and emotional problems. This community service activity is about educating the impact of using gadgets on the socio-economic behavior of elementary school aged children at SD Negeri 1 Ambon which is expected to shape the character of students who have creativity and cognitive abilities in using gadgets responsibly. This socialization activity was carried out on October 31 2024 using an outreach method attended by 50 grade 5 and grade 6 students. The results of this socialization activity showed an increase in understanding of using gadgets responsibly and students were able to answer questions well from the presenters.